Quantitative Comparison of Soil Transmitted Helminths (STH) Eggs Flotation Method with Different Solutions and Times - Chairil Anam, Ardian; Ghofur, Abdul (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Soil-Transmitted Helminths (STH) infections are among the most common communicable diseases worldwide and have a significant impact on public health. These infections are caused by several types of intestinal worms, including Ascaris lumbricoides, Trichuris trichiura, Strongyloides stercoralis, Necator americanus, and Ancylostoma duodenale. Children and individuals working in agriculture are particularly at high risk of infection. The flotation method is commonly used to detect helminth eggs in stool samples. This study aimed to assess the effectiveness of the flotation method using different solutions—NaCl, ZnSO₄, and MgSO₄—at incubation times of 30 minutes and 40 minutes in detecting the number of STH eggs. Method: This study used an experimental design, where the researchers applied different flotation solutions and incubation times. The results were statistically analyzed using the MANOVA test. Results: The MANOVA test showed that all significance values were > 0.05, indicating no statistically significant effect of the different flotation solutions and incubation times on the quantitative detection of STH eggs. However, descriptive analysis revealed that the ZnSO₄ solution with 40 minutes of incubation was more effective than NaCl and MgSO₄, as it detected a higher number of STH eggs. Conclusion: It can be concluded that there is no statistically significant effect of the flotation method using different solutions and incubation times on the quantitative detection of Soil-Transmitted Helminth eggs. Nonetheless, ZnSO₄ with 40 minutes of incubation showed relatively better descriptive results.